Empowering Disadvantaged Communities in the UK: Missing the Potential of Co-production. (June 2019) - Booth, Jane
Co-production is a model of service delivery aimed at engaging disadvantaged communities to generate a more responsive approach to the design of local services. Such a shift implies the empowerment of disadvantaged communities, transforming them from 'passive' recipients of services to more active citizens. However, its potential to enhance citizenship in the UK is becoming lost in the political landscape of austerity and neoliberalism, with behaviour change being imposed on disadvantaged communities rather than enabled through a genuine sharing of power. If co-production is to fulfil its potential, it requires not only disadvantaged communities to engage but also a transformation of the paternalistic professional practices and institutional cultures that reproduce the power relationship between service users and service providers. Furthermore, without engaging citizens in ideological debate, making visible the systemic nature of inequalities, it is hard to see how co-production can bring about the social change it implies.